Analisa Perancangan Sistem Persediaan Bahan Baku Pada Perusahaan Farmasi - Nauli, Sukarno Bahat (Jurnal Ilmiah FIFO, 2019)
The development of technology in the field of information encourages each agency or company to keep abreast of its development, especially with regard to the development of information technology that has to do with the activities of the company. Pharmaceutical companies which produce drugs to provide goods for pharmacies and hospitals are very important to record the availability of drugs that are still feasible and drugs that have expired. So that the drug supply can be maintained and can be distributed with the needs of the drug properly. This study aims to design a Raw Material Inventory Information System in Pharmaceutical Companies to solve problems that occur in the current system. Raw Material Inventory System Design in Pharmaceutical Companies using Data Base Design and System Interface Design.